2015
DOI: 10.1515/opli-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal analysis of quotation in oral narratives

Abstract: Abstract:We investigate direct speech quotation in informal oral narratives by analyzing the contribution of bodily articulators (character viewpoint gestures, character facial expression, character intonation, and the meaningful use of gaze) in three quote environments, or quote sequences -single quotes, quoted monologues and quoted dialogues -and in initial vs. non-initial position within those sequences. Our analysis draws on findings from the linguistic and multimodal realization of quotation, where multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…As Stec et al (2015) demonstrate, however, in one of the few detailed studies of multimodality in reported speech, no multimodal signal in reported speech plays a conventional role that compares to morphosyntactic expression (also cf. Malibert & Vanhove 2015).…”
Section: Reported Speech Constructions Are Conditioned By Grammarmentioning
confidence: 98%
See 1 more Smart Citation
“…As Stec et al (2015) demonstrate, however, in one of the few detailed studies of multimodality in reported speech, no multimodal signal in reported speech plays a conventional role that compares to morphosyntactic expression (also cf. Malibert & Vanhove 2015).…”
Section: Reported Speech Constructions Are Conditioned By Grammarmentioning
confidence: 98%
“…Although claims about the contribution of such signals are rarely quantified, they have given rise to a view in which reported speech is a 'multimodal' phenomenon, which is not signalled through language structure per se, but is equally created through special gestures and voice quality (Blackwell et al 2015;Dancygier & Sweetser 2012;Lampert 2013;Stec et al 2015). The implication of these accounts is that morphosyntactic marking is just one of a range of linguistic and extra-linguistic signals that contribute to the expression of reported speech.…”
Section: Reported Speech Constructions Are Conditioned By Grammarmentioning
confidence: 99%
“…While we do not claim that any of the aspects of our analysis is entirely novel, our analysis departs in important ways from more traditional analyses and several recent accounts of un(der)marking perspective shift. Our semantic definition of framing relies heavily on earlier semantic descriptions of reported speech (see Spronck 2017 for a fuller literature review), and the approach to optionality is primarily indebted to McGregor (2013), but it provides an alternative to a recently popular school of thought that situates the meaning of reported speech outside 'core' grammar (Blackwell, Perlman, and Tree 2015;Dancygier 2016;D'Arcy 2015;Lampert 2013;Stec, Huiskes, and Redeker 2015). Faced with common examples, such as the free indirect speech construction in (1), or the frequency and regularity of suprasegmental and extra-linguistic signals in the expression of reported speech, such as eye-gaze or voice quality, these accounts arrive at the conclusion that reported speech cannot be characterised at a morpho-syntactic level alone.…”
Section: Defenestrationmentioning
confidence: 99%
“…Although gestures, eye-gaze, voice quality etc. occur in patterns, most of these are actually not that clearly conventionalised (Stec, Huiskes, and Redeker 2015), and such observations are puzzling if the assumption is that linguistic semantic interpretation relies on them. The underlying assumption, that a meaning must be marked somehow, combined with the finding that marking is imperfectly conventionalised, then leads to the dramatic conclusion that grammar itself is an unreliable indicator of linguistic meaning, in reported speech and, possibly, beyond.…”
Section: Defenestrationmentioning
confidence: 99%
“…Multimodal co-articulation has been associated with the function of quotations as demonstrations (Clark & Gerrig 1990;Bavelas et al 2014), depictions (Clark 2016), (re)enactments (Streeck 2002;Sidnell 2006) and viewpoint shifts (McNeill 1992;Dancygier & Sweetser 2012;Stec et al 2015;. In studies of signed languages, the concepts of role shift, constructed dialogue, constructed action, or perspective shift are used for the representation of actions, thoughts and feelings of narrative characters via manual and non-manual means, such as the systematic use of gaze, facial portrayals and sign space to manage narrative structure (see Metzger 1995;Quinto-Pozos 2007;Janzen 2012; comparative studies of speakers and signers include Rayman 1999;Marentette et al 2004;Earis & Cormier 2013).…”
Section: Introductionmentioning
confidence: 99%